Heat transfer through a hybrid wall attachment with a water-cooled absorber - Escoto, Angela Diso (2001)
This study investigates the heat transfer through a tube and s sheet assembly reffered to as the hybrid wall attachment configured using horizontal, parallel copper tubes attached to an aluminum sheet. The final objective is to prevent or at least minimize warming up of concrete walls that are exposed to solar irradiation. To this end, the metal sheet assembly will eventually be attached to the external surface of the concrete wall and direct cooling can be achieved by pumping water through the tubes. This heat transfer study involves the determination of the following parameters for the hybrid wall attachement: (1) system time constant, (2) achievable cooling indicated by the final temperature of the sheet, (3) heat transfer coefficients for convective heat loss to the ambient air loss to water, (4) temperature profiles across the metal sheet, (5) recommended tube spacing and (6) water flow rate. Mathematical models for the time variations of the sheet temperature during flow and for the case of no water flow were developed and compared with experimental data. Numerical solutions to the partial differential equations using an explicit method were used to map the temperature profiles of the sheet, Suggested mathematical equations for the solar flux and ambient temperature variations with time for local conditions were also obtained. From the results, theoretical predictions of the wall performance were made and the advantages/disadvantages in connection with its use were assessed.
Thesis (Ph.D. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Heat -- Transmission; Heat -- Radiation and absorption; Exterior walls -- Thermal properties; Metals -- Thermal properties